2021
DOI: 10.1111/1471-0528.16602
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre‐eclampsia definitions on the identification of adverse outcome risk in hypertensive pregnancy – analyses from the CHIPS trial (Control of Hypertension in Pregnancy Study)

Abstract: Objective To examine the association between pre‐eclampsia definition and pregnancy outcome. Design Secondary analysis of Control of Hypertension in Pregnancy Study (CHIPS) trial data. Setting International multicentre randomised controlled trial (RCT). Population In all, 987 women with non‐severe non‐proteinuric pregnancy hypertension. Methods We evaluated the association between pre‐eclampsia definitions and adverse pregnancy outcomes, stratified by hypertension type and blood pressure control. Main outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…This diagnostic shift will influence clinical management (for example, increased hospital admission and induction of labour) 17 . Although the debate is still ongoing on these new classification systems, studies published in 2021 revealed that a broad definition of pre-eclampsia could better identify women and babies at risk of adverse outcomes 22 , 23 .…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…This diagnostic shift will influence clinical management (for example, increased hospital admission and induction of labour) 17 . Although the debate is still ongoing on these new classification systems, studies published in 2021 revealed that a broad definition of pre-eclampsia could better identify women and babies at risk of adverse outcomes 22 , 23 .…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…A recurring theme in prospective studies 54,55 is that compared with a narrow definition (ie, hypertension and proteinuria), a broad definition has a higher sensitivity for identifying women who suffer complications but a lower specificity. Authors have supported this, as "the purpose of classification is to identify groups of women who require specific care," 55 such as closer monitoring.…”
Section: Future Criteriamentioning
confidence: 99%
“…PE is a human pregnancy disorder clinically manifesting with new-onset hypertension after 20 weeks of gestation ( Magee et al, 2021 ). Proteinuria is a common symptom of PE; however, it is not a criterion for diagnosis ( Brown et al, 2018 ; Magee et al, 2021 ).…”
Section: Preeclampsiamentioning
confidence: 99%
“…PE is a human pregnancy disorder clinically manifesting with new-onset hypertension after 20 weeks of gestation ( Magee et al, 2021 ). Proteinuria is a common symptom of PE; however, it is not a criterion for diagnosis ( Brown et al, 2018 ; Magee et al, 2021 ). End-organ dysfunctions such as acute kidney injury, neurological symptoms, liver dysfunction, the HELLP syndrome (Hemolysis, Elevated Liver enzymes, Low Platelets), and/or uteroplacental dysfunction, such as fetal growth restriction (FGR), may also feature in PE ( Brown et al, 2018 ; Magee et al, 2021 ).…”
Section: Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation